Pirarucu growth under different feeding regimes - Gandra, André Lima; Ituassú, Daniel Rabello; Pereira Filho, Manoel; Roubach, Rodrigo; Crescêncio, Roger; Cavero, Bruno Adan Sagratzki (Aquaculture International, 2007)
In order to assess the most suitable feeding schedule for pirarucu, Arapaima gigas, we placed groups of seven fish in 12 1-m3 cages and investigated various feeding variables in a 2 × 2 factorial design. The feeding variables analyzed were one feeding (OC) or two feedings (TW), feeding daily (1D) or every other day (2D), and their interactions: one feeding once per day (OC/1D), two feedings per day (TW/1D), one feeding every other day (OC/2D) and two feedings every other day (TW/2D). The experiment lasted for 45 days, and the fish were maintained on a commercial extruded diet. The results showed similar final weights between fish maintained on feedings OC and TW, but higher ones in fish fed 1D than 2D. Weight gain was higher when the fish were fed TW and 1D. Apparent feed conversion was not affected in fish fed OC or TW and 1D or 2D. Daily feed consumption was also higher for the feeding schedules of TW and 1D. The combination of feeding schedules produced higher final weights and weight gains for fish fed OC/1D and TW/1D. The apparent feed conversion value was higher only in fish fed TW/1D. Daily feed consumption values were significantly higher in fishes fed TW/1D. The lowest value was recorded for OC/2D. © Springer Science+Business Media, Inc. 2006.
Keywords: Aquaculture; Commercial Species; Feeding; Fish Culture; Fishery Management; Arapaima Gigas; Pisces